2020
DOI: 10.12688/f1000research.25247.2
|View full text |Cite
|
Sign up to set email alerts
|

Alleviative effects of Fara-darmani Consciousness Field on Triticum aestivum L. under salinity stress

Abstract: Background: The Fara-darmani Consciousness Field was founded by Mohammad Ali Taheri. It is a novel field and is described similarly to the field of gravity, or the electromagnetic field. This field is neither matter nor energy, and therefore does not possess a quantity. Even though there is no direct scientific evidence for the Consciousness Field, it is possible to investigate its effects on objects through controlled experiments. The aim of the present work was to study the alleviative effects of the Fara-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Further details about the theory of CFs are discussed in recent articles (Taheri et al, 2020a). In this way, it has been reported that FCF alleviated the adverse effects of salt stress on wheat plants (Torabi et al, 2020). Other observations that have used this method include the effects of FCF in changing cancer cell growth patterns (Taheri et al, 2020b), behaviors and biochemical alterations of Alzheimer's disease rat models (Taheri et al 2021b), and the electrical activities of the brain (Taheri, et al, 2020c).…”
Section: Introductionmentioning
confidence: 99%
“…Further details about the theory of CFs are discussed in recent articles (Taheri et al, 2020a). In this way, it has been reported that FCF alleviated the adverse effects of salt stress on wheat plants (Torabi et al, 2020). Other observations that have used this method include the effects of FCF in changing cancer cell growth patterns (Taheri et al, 2020b), behaviors and biochemical alterations of Alzheimer's disease rat models (Taheri et al 2021b), and the electrical activities of the brain (Taheri, et al, 2020c).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, remarkable restorative-enhancing effects were observed in their passive avoidance behavior. Changes in cancer cell growth [31], investigations on electrical activity of the brain during FCF connection in Faradarmangar [32], and alleviative effects of FCF on wheat plant under salt stress [33] are other observations that have used this method in research. The aim of the present study was to investigate the in uence of the FCF on AD cells and animal models.…”
Section: Introductionmentioning
confidence: 99%